As you like it: Understanding the relationship between packing design and accessibility. Issue 10 (10th July 2019) - Yoxall, Alaster; Gonzalez, Victor; Best, Joshua; Rodriguez‐Falcon, Elena M.; Rowson, Jennifer
Abstract : Accessible packaging is continually receiving greater attention as an ageing population becomes a primary driver behind inclusive design. As we age, our strength dexterity and some cognitive functions decline. For this reason, the ease of interaction with simple tasks in daily living becomes an ever increasing concern. ISO 17480 "Packaging Guidelines" consider capability issues relating to packaging and ageing to broadly come under three areas, namely, strength, dexterity, and cognition. Significant previous work has been undertaken looking at the issue of strength on packaging accessibility, with fewer studies looking at the relationship between the physical demands of dexterity and the understanding of how to open the pack. In this previous work, there has been little attempt to quantify the effect of the affordances, perceptual information and symbology, and the physical demands of the pack and how this relates to accessibility. Hence, this exploratory study seeks to use motion capture and a dexterity test, along with a cognitive demand test to study this relationship and any changes with age. This research indicates that the dexterous demands of a task are linked to the cognitive demands; and thus in reaching a level of comprehension of the pack and how to access the product a subject may interact with a pack effectively. Abstract : Accessible packaging is continually receiving greater attention as an ageing population becomes a primary driver behind inclusive design. This paper attempts to quantify the effect of the affordances, perceptual information, and symbology and the physical demands of the pack and how this relates to accessibility.